Lyotard reframed interpreting key thinkers for the arts - Jones, Graham (I.B.Tauris, 2014)
Lyotard's thoughts on the postmodern have often been misunderstood or misrepresented.'Lyotard Reframed'provides a clear and original introduction to Lyotard's work on the postmodern and his philosophy more generally, demonstrating its on-going relevance to creative endeavour and debates concerning the value and significance of the visual arts. It also situates Lyotard's discussion of the postmodern in the context of his other key concepts: the Figural, the Libidinal, and the Sublime. Written for students, teachers and those interested in the arts more generally,'Lyotard Reframed'employs numerous examples drawn from painting, cinema, and comic books, to illustrate the significance of these ideas and to explore their links with phenomenology, Marxism, structuralism, psychoanalysis and deconstruction. It also presents a glossary of relevant concepts and a useful guide to further reading.